El signo ebrio:El árbol de Saussure de Héctor Libertella - Diego Vecchio (Cuadernos LIRICO, 2020)
This article deals with the relationship between linguistics, psychoanalysis and literature: the friction-laden crossover of the unconscious to language over three distinct time periods. First, the beginning of the 20th century when, as Ferdinand Saussure is studying anagrams in Indo-European poetry, Theodore Flournoy asks him to evaluate the somnambulist glossolalia produced by the medium Hélène Smith. Then, the middle of the 20th century, when Jacques Lacan, in the wake of structuralism, revises the Saussurean linguistic sign from the perspective of the Freudian unconscious. Finally, at the end of the 20h century, when Hector Libertella reinvents the hermetic vanguard through a reading of Lacanian theory, wittily recasting in his theoretical fiction El árbol de Saussure the linguistic sign as the inebriated sign.